Study of the Relationship of e-WOM to Purchase Decision and Brand Image as A Mediation Variable - Eko Handayanto; Iqbal Ramadhani Fuadiputra (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to examine the influence of Electronic Word of Mouth (e-WOM) on Purchase Decisions, with Brand Image serving as a mediating variable, focusing on Torch Bag products in the Malang region. Utilizing a quantitative research approach, data were collected through structured questionnaires from 150 respondents and analyzed using the Structural Equation Modeling - Partial Least Squares (SEM-PLS) method. The findings reveal that e-WOM significantly affects both Brand Image and Purchase Decisions. Moreover, Brand Image has a strong positive impact on Purchase Decisions and also acts as a partial mediator in the relationship between e-WOM and purchasing behavior. This indicates that positive online reviews and consumer interactions not only build trust and enhance a brand's image but also significantly influence the final purchasing decision. The study contributes to the growing literature on digital consumer behavior and highlights the importance of managing online presence and consumer-generated content. For marketers, the results suggest that investing in strategies to stimulate and manage e-WOM can enhance brand perception and drive sales. Maintaining a consistent and positive brand image through online platforms is crucial in today's competitive digital market landscape.